Analisis efektivitas relatif metode kontrasepsi dari data survei prevalensi Indonesia, 1987 (Badan Koordinasi Keluarga Berencana Nasional, 1991)
Relative effectiveness of contraceptive methods in Indonesia based on the data of the 1987 national contraceptive prevalence survey.